Airway replacement using stented aortic matrices: Long‐term follow‐up and results of the TRITON‐01 study in 35 adult patients. Issue 12 (14th July 2022) - Martinod, Emmanuel; Radu, Dana M.; Onorati, Ilaria; Portela, Ana Maria Santos; Peretti, Marine; Guiraudet, Patrice; Destable, Marie‐Dominique; Uzunhan, Yurdagül; Freynet, Olivia; Chouahnia, Kader; Duchemann, Boris; Kabbani, Jamal; et al.
Abstract : Over the past 25 years, we have demonstrated the feasibility of airway bioengineering using stented aortic matrices experimentally then in a first‐in‐human trial ( n = 13). The present TRITON‐01 study analyzed all the patients who had airway replacement at our center to confirm that this innovative approach can be now used as usual care. For each patient, the following data were prospectively collected: postoperative mortality and morbidity, late airway complications, stent removal and status at last follow‐up on November 2, 2021. From October 2009 to October 2021, 35 patients had airway replacement for malignant ( n = 29) or benign ( n = 6) lesions. The 30‐day postoperative mortality and morbidity rates were 2.9% ( n = 1/35) and 22.9% ( n = 8/35) respectively. At a median follow‐up of 29.5 months (range 1–133 months), 27 patients were alive. There have been no deaths directly related to the implanted bioprosthesis. Eighteen patients (52.9%) had stent‐related granulomas requiring a bronchoscopic treatment. Ten among 35 patients (28.6%) achieved a stent free survival. The actuarial 2‐ and 5‐year survival rates (Kaplan–Meier estimates) were respectively 88% and 75%. The TRITON‐01 study confirmed that airway replacement using stented aortic matrices can be proposed as usual care at our center. Clinicaltrials.gov Identifier: NCT04263129. Abstract : The TRITON‐01 study confirms that airway replacement using stented aortic matrices can be proposed as usual care. Patterson and Rendina comments page 2721 .